An arc-proof fabric with a flame-retardant function, a preparation method and application thereof

CN122960018APending Publication Date: 2026-10-23SWOTO PROTECTION & TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611260019.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,该技术方案在实际应用中仍存在以下亟待解决的问题:首先,壳聚糖磷酸盐与丁烷四羧酸在同一处理液中直接混合,壳聚糖分子链上大量未参与磷酸化的羟基和氨基在焙烘过程中会与丁烷四羧酸的多个羧基发生非特异性酯化反应,一方面消耗了本该用于与纤维素交联的羧基,降低了交联效率;另一方面,过度交联使得壳聚糖的成炭骨架被刚性锁定,遇火时难以充分膨胀展开,限制了其成炭阻隔效果的发挥;其次,丁烷四羧酸的四个羧基反应活性差异不大,在催化条件下与纤维素羟基的交联点分布过于密集均匀,所形成的酯键网络缺乏柔性链段作为应力缓冲区域,导致织物手感僵硬,且在高温冲击下交联网络易发生脆性断裂;且该发明并未对柔软剂进行阻燃功能化改性,常规柔软剂的引入会与阻燃剂和交联剂产生功能互斥,难以在保证阻燃效率的同时兼顾织物的柔软手感和穿着舒适性

Benefits of technology

本申请提供的具有阻燃功能的防电弧面料通过将防电弧面料基布依次在改性硅酸壳聚糖阻燃剂水溶液、改性丁烷四羧酸交联剂水溶液和改性磷氮系阻燃亲水柔软剂水溶液中进行浸渍处理后得到,通过限定所述改性硅酸壳聚糖阻燃剂水溶液、改性丁烷四羧酸交联剂水溶液以及改性磷氮系阻燃亲水柔软剂水分散液的具体组成,使最终所得电弧面料兼具高效阻燃性、高断裂强力、优异的柔软手感及优异的耐水洗性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of textiles and relates to an anti-electric-arc fabric with a flame-retardant function and a preparation method and application thereof. The anti-electric-arc fabric with a flame-retardant function is obtained by sequentially immersing an anti-electric-arc fabric base cloth in a modified silicic acid chitosan flame retardant aqueous solution, a modified butane tetracarboxylic acid crosslinking agent aqueous solution and a modified phosphorus-nitrogen flame-retardant hydrophilic softener aqueous dispersion. By limiting the specific compositions of the modified silicic acid chitosan flame retardant aqueous solution, the modified butane tetracarboxylic acid crosslinking agent aqueous solution and the modified phosphorus-nitrogen flame-retardant hydrophilic softener aqueous dispersion, the final obtained electric-arc fabric has high efficient flame retardancy, high breaking strength, excellent soft hand feeling and excellent washing resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of textile technology and relates to an arc-resistant fabric with flame-retardant function, its preparation method and application. Background Technology

[0002] Arc-resistant fabrics refer to special protective fabrics used in high-risk environments such as power operations, petrochemicals, and metal smelting, which can effectively resist the high temperature, strong light, and pressure impact generated by electric arc explosions. Flame-retardant composites are fabrics that, through multi-component and multi-step synergistic finishing, construct a composite functional system including a flame-retardant layer, a cross-linking and fixing layer, and a functional modification layer on the fabric base, giving the fabric multiple protective and comfort properties such as flame retardancy, washability, softness, and moisture permeability.

[0003] Among numerous flame retardant systems, chitosan (CTS), as a natural biomass polymer, is considered a highly promising environmentally friendly flame retardant due to its rich hydroxyl and amino groups in its molecular chain, exhibiting excellent char-forming properties and biocompatibility. However, the abundant hydroxyl and amino groups on the chitosan molecular chain undergo non-specific esterification reactions with polycarboxylic acid crosslinking agents under high-temperature baking conditions. This not only consumes the effective functional groups of the crosslinking agent but also leads to the over-crosslinking and locking of the flame retardant's own char-forming skeleton, resulting in a loss of expansion space. In formaldehyde-free crosslinking finishing systems, 1,2,3,4-butanetetracarboxylic acid (BTCA) is currently recognized as the formaldehyde-free crosslinking agent with the highest crosslinking efficiency. However, its four carboxyl groups exhibit highly uniform reactivity with cellulose under catalytic conditions, resulting in an overly dense and uniform distribution of crosslinking points. The resulting ester bond network lacks stress buffer regions, making it prone to brittle fracture under the high-temperature impact of electric arc combustion. Simultaneously, the strongly acidic catalytic environment of the crosslinking agent exacerbates the hydrolytic breakage of cellulose glycoside bonds, causing a loss of fabric strength.

[0004] To address the aforementioned shortcomings, existing technologies attempt to incorporate chitosan into the BTCA finishing system. For example, CN104911910A discloses a method for preparing cellulose fabrics with both antibacterial and flame-retardant functions. This technique dissolves chitosan phosphate in a BTCA solution and adds sodium hypophosphite as a catalyst, achieving functional finishing of the fabric through a padding-baking process. This approach utilizes the flame-retardant catalytic effect of chitosan phosphate and the cross-linking properties of BTCA, achieving a certain degree of synergy between antibacterial and flame-retardant properties. However, this technical solution still faces the following problems in practical applications: First, when chitosan phosphate and butanetetracarboxylic acid are directly mixed in the same treatment solution, a large number of unphosphorylated hydroxyl and amino groups on the chitosan molecular chain will undergo non-specific esterification reactions with multiple carboxyl groups of butanetetracarboxylic acid during baking. On the one hand, this consumes the carboxyl groups that should be used for crosslinking with cellulose, reducing the crosslinking efficiency. On the other hand, excessive crosslinking makes the char-forming skeleton of chitosan rigidly locked, making it difficult to fully expand and unfold when exposed to fire, thus limiting its char-forming barrier effect. Second, the four carboxyl groups of butanetetracarboxylic acid have similar reactivity. Under catalytic conditions, the crosslinking points with cellulose hydroxyl groups are too densely and uniformly distributed. The resulting ester bond network lacks flexible chain segments as stress buffer regions, resulting in a stiff fabric feel. Furthermore, the crosslinking network is prone to brittle fracture under high-temperature impact. Moreover, this invention does not perform flame-retardant functional modification on the softener. The introduction of conventional softeners will result in functional incompatibility with flame retardants and crosslinking agents, making it difficult to ensure both flame-retardant efficiency and the soft feel and wearing comfort of the fabric.

[0005] Therefore, providing an arc-resistant fabric that combines high flame retardancy, high tensile strength, excellent softness and washability to solve the problem of balancing protective performance, mechanical properties and wearing comfort in the existing technology is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the purpose of this application is to provide an arc-resistant fabric with flame-retardant properties, its preparation method, and its application. The arc-resistant fabric combines high flame retardancy, high tensile strength, excellent softness, and excellent washability.

[0007] To achieve this objective, the present application adopts the following technical solution: In a first aspect, this application provides an arc-resistant fabric with flame-retardant function, which is obtained by impregnating the arc-resistant fabric base fabric in a modified silica chitosan flame retardant aqueous solution, a modified butane tetracarboxylic acid crosslinking agent aqueous solution and a modified phosphorus nitrogen flame retardant hydrophilic softener aqueous dispersion. The raw materials for the modified silicate chitosan flame retardant aqueous solution include chitosan, tetraethyl orthosilicate, polyethyleneimine, silane coupling agent, phytic acid, and water. The raw materials for the modified butanetetracarboxylic acid crosslinking agent aqueous solution include butanetetracarboxylic acid, sodium hypophosphite, citric acid, polyethylene glycol, N-hydroxysuccinimide, and water; The raw materials for the modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion include amino silicone oil, epichlorohydrin, phosphate quaternary ammonium salt glycerol ether, isocyanate propyltriethoxysilane, polyetheramine and water.

[0008] The flame-retardant arc-resistant fabric provided in this application is obtained by sequentially padding the arc-resistant fabric base fabric in an aqueous solution of modified silicate chitosan flame retardant, an aqueous solution of modified butane tetracarboxylic acid crosslinking agent, and an aqueous dispersion of modified phosphorus nitrogen flame retardant hydrophilic softener. The modified silicate chitosan flame retardant aqueous solution contains chitosan, tetraethyl orthosilicate, polyethyleneimine, silane coupling agent, phytic acid, and water. Chitosan is grafted with tetraethyl orthosilicate sol-gel to introduce inorganic silicon components, forming an organic-inorganic hybrid framework. This inhibits the pyrolysis and breakage of the chitosan backbone at high temperatures. Simultaneously, in-situ graft polymerization of phytic acid introduces high-density phosphate groups onto the molecular chain, catalyzing char formation and forming an intumescent char layer upon contact with fire. The three-dimensional cross-linked network constructed by polyethyleneimine firmly anchors the flame retardant structure with chemical bonds, preventing migration and loss of the flame retardant during washing. The silane coupling agent further improves the compatibility of the organic-inorganic interface, ensuring the uniformity and stability of the hybrid structure. This solves the problems of poor thermal stability, low char formation rate, and weak bonding with fibers inherent in conventional chitosan flame retardants.

[0009] The raw materials for the modified butanetetracarboxylic acid crosslinking agent aqueous solution include butanetetracarboxylic acid, sodium hypophosphite, citric acid, polyethylene glycol, N-hydroxysuccinimide, and water. Butanetetracarboxylic acid reacts with citric acid under the catalysis of sodium hypophosphite to form a complex polycarboxylic acid system, which effectively reduces the melting point of single 1,2,3,4-butanetetracarboxylic acid (BTCA) and improves solution stability. Polyethylene glycol is partially grafted into the crosslinking agent molecular chain by esterification, embedding flexible polyether segments, avoiding excessively dense and uniform distribution of crosslinking points that leads to stress concentration, and giving the crosslinking network stress buffering ability. The activated esterification of N-hydroxysuccinimide can significantly improve the reaction selectivity between carboxyl groups and cellulose hydroxyl groups, widening the baking temperature window while reducing acid hydrolysis damage to cellulose, thus solving the problems of fabric stiffness, severe strength reduction, and harsh reaction conditions caused by conventional 1,2,3,4-butanetetracarboxylic acid crosslinking.

[0010] The modified phosphorus-nitrogen flame-retardant hydrophilic softener aqueous dispersion contains amino silicone oil, epichlorohydrin, phosphate quaternary ammonium glycerol ether, isocyanate propyltriethoxysilane, polyetheramine, and water. The amino silicone oil undergoes ring-opening grafting with epichlorohydrin to block the active hydrogen on the side chains, effectively inhibiting yellowing at high temperatures. The phosphate quaternary ammonium glycerol ether introduces both phosphorus-nitrogen flame-retardant elements and quaternary ammonium hydrophilic groups into the silicone oil molecule through chemical bonds, avoiding the problem of independent and mutually exclusive functions of flame retardants and softeners in traditional physical compounding. The isocyanate propyltriethoxysilane end-capping introduces hydrolyzable crosslinkable siloxane groups, and the polyetheramine chain extension further supplements the hydrophilic segments, enabling the softener to contribute to the fabric's soft feel while also providing flame retardancy and hydrophilic conductivity. After baking, it forms a covalently bonded network with fibers and crosslinking agents, exhibiting superior wash resistance compared to conventional physically adsorbed softeners.

[0011] In summary, by limiting the specific composition of the modified silicate chitosan flame retardant aqueous solution, the modified butanetetracarboxylic acid crosslinking agent aqueous solution, and the modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion, the final arc-resistant fabric possesses high flame retardancy, high tensile strength, soft hand feel, and excellent washability.

[0012] In some specific embodiments, the mass percentage of modified silicate chitosan flame retardant in the aqueous solution of the modified silicate chitosan flame retardant is 5-15%, such as 6%, 7%, 8%, 9%, 10%, 12% or 14%.

[0013] In some specific embodiments, the modified silicate chitosan flame retardant is prepared by grafting chitosan with tetraethyl orthosilicate sol-gel, constructing a polyethyleneimine crosslinked network, surface coupling with a silane coupling agent, and in-situ grafting polymerization with phytic acid.

[0014] In some specific embodiments, the mass ratio of tetraethyl orthosilicate to chitosan is 1:(2~4), for example 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8 or 1:4, etc.

[0015] In some specific embodiments, the mass ratio of polyethyleneimine to chitosan is 1:(3~6), such as 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5 or 1:6.

[0016] In some specific embodiments, based on the mass of the chitosan as 100%, the amount of the silane coupling agent is 3-5%, such as 3%, 3.5%, 4%, 4.5% or 5%.

[0017] In some specific embodiments, the silane coupling agent includes any one or a combination of at least two of γ-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, or aminopropyltriethoxysilane.

[0018] In some specific embodiments, the mass ratio of phytic acid to chitosan is 1:(3~5), such as 1:3, 1:3.5, 1:4, 1:4.5 or 1:5.

[0019] In some specific embodiments, the preparation method of the modified silicate chitosan flame retardant includes the following steps: (A1) Chitosan is dissolved in an aqueous acetic acid solution to prepare a chitosan solution with a mass percentage of 4-6% (e.g., 4%, 4.5%, 5%, 5.5%, or 6%). Tetraethyl orthosilicate is added, and the mixture is stirred at 40-60°C (e.g., 40°C, 45°C, 50°C, 55°C, or 60°C) for 2-4 h (e.g., 2 h, 2.5 h, 3 h, 3.5 h, or 4 h). The silica sol generated by the hydrolysis of tetraethyl orthosilicate is grafted onto the chitosan molecular chain through hydrogen bonds and chemical bonds to obtain silica sol-grafted chitosan. (A2) Polyethyleneimine is added to the obtained silica sol grafted chitosan, and the mixture is stirred at 60~80℃ (e.g. 60℃, 65℃, 70℃, 75℃ or 80℃, etc.) for 2~4 h (e.g. 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc.). The amino groups of polyethyleneimine react with the hydroxyl groups on the chitosan molecular chain and the silanol groups on the surface of the silica sol to form a three-dimensional network structure, and a polyethyleneimine cross-linked silica chitosan complex is obtained. (A3) Add a silane coupling agent to the obtained silica-chitosan composite and stir the mixture at 50-70℃ (e.g., 50℃, 55℃, 60℃, 65℃ or 70℃, etc.) for 1-2 h (e.g., 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h or 2 h, etc.) to allow the epoxy groups of the silane coupling agent to undergo ring-opening addition reactions with the amino and hydroxyl groups on chitosan and polyethyleneimine. At the same time, the methoxy groups of the silane coupling agent hydrolyze and condense to form siloxane crosslinking nodes, thus obtaining a surface-coupled modified composite flame-retardant precursor. (A4) Phytic acid is added to the obtained composite flame retardant precursor and stirred at 70~90℃ (e.g. 70℃, 75℃, 80℃, 85℃ or 90℃, etc.) for 2~3 h (e.g. 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h, etc.). The phosphate groups of phytic acid undergo esterification graft polymerization with the hydroxyl groups on the chitosan molecular chain, introducing flame retardant segments with high phosphorus content in situ on the surface of the composite and inside the network. Finally, after filtration, washing and vacuum drying, the modified silicate chitosan flame retardant is obtained.

[0020] In some specific embodiments, the mass percentage of the acetic acid aqueous solution in step (A1) is 3-5%, such as 3%, 3.5%, 4%, 4.5% or 5%.

[0021] In some specific embodiments, the mass percentage of the modified butanetetracarboxylic acid crosslinking agent in the aqueous solution of the modified butanetetracarboxylic acid crosslinking agent is 8-12%, such as 8.5%, 9%, 9.5%, 10%, 10.5%, 11% or 11.5%.

[0022] In some specific embodiments, the modified butanetetracarboxylic acid crosslinking agent is prepared by butanetetracarboxylic acid through sodium hypophosphite catalysis, co-reaction with citric acid, polyethylene glycol esterification grafting, and N-hydroxysuccinimide activation esterification treatment.

[0023] In some specific embodiments, the mass ratio of sodium hypophosphite to butanetetracarboxylic acid is 1:(5~8), such as 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5 or 1:8.

[0024] In some specific embodiments, the mass ratio of citric acid to butanetetracarboxylic acid is 1:(4~6), such as 1:4, 1:4.5, 1:5, 1:5.5 or 1:6.

[0025] In some specific embodiments, the mass ratio of polyethylene glycol to butanetetracarboxylic acid is 1:(10~15), such as 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.

[0026] In some specific embodiments, the molar ratio of N-hydroxysuccinimide to butanetetracarboxylic acid is 1:(3~5), such as 1:3, 1:3.5, 1:4, 1:4.5 or 1:5.

[0027] In some specific embodiments, the preparation method of the modified butanetetracarboxylic acid crosslinking agent includes the following steps: (B1) Dissolve butanetetracarboxylic acid in deionized water to prepare a solution with a mass percentage of 15-25% (e.g., 15%, 17%, 19%, 21%, 23%, or 25%), add sodium hypophosphite, adjust the pH to 3.5-4.5 (e.g., 3.5, 3.7, 3.9, 4.1, 4.3, or 4.5), and stir to dissolve at 60-80°C (e.g., 60°C, 65°C, 70°C, 75°C, or 80°C) to obtain a catalytic activation system; (B2) Add citric acid to the obtained catalytic activation system and stir at 75-95℃ (e.g., 75℃, 80℃, 85℃, 90℃, or 95℃, etc.) for 1.5-3 h (e.g., 1.5 h, 1.7 h, 1.9 h, 2.1 h, 2.3 h, 2.5 h, 2.7 h, 2.9 h, or 3 h, etc.). Citric acid and butanetetracarboxylic acid form a complex polycarboxylic acid system through intermolecular hydrogen bonding and partial esterification, lowering the melting point of the system and improving water solubility. After cooling to 50-65℃ (e.g., 50℃, 52℃, 54℃, 56℃, 58℃, 60℃, 62℃, or 65℃, etc.), add polyethylene glycol and stir for 40-60 min (e.g., 40 min, 45 min, 50 min, 55 min, etc.). (e.g., min or 60 min), the terminal hydroxyl groups of polyethylene glycol undergo a partial esterification reaction with the carboxyl groups of polycarboxylic acids, introducing flexible polyether segments into the crosslinking agent molecule structure to obtain a polyethylene glycol graft-modified composite crosslinking agent; (B3) Add N-hydroxysuccinimide to the obtained composite crosslinking agent and stir at 40-60℃ (e.g., 40℃, 45℃, 50℃, 55℃, or 60℃) for 30-60 min (e.g., 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, or 60 min). N-hydroxysuccinimide forms an active ester intermediate with some of the carboxyl groups of butanetetracarboxylic acid, which improves the esterification reaction activity between the carboxyl groups and the cellulose hydroxyl groups. Then cool to room temperature at a rate of 5-10℃ / min (e.g., 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, or 10℃ / min) to obtain the modified butanetetracarboxylic acid crosslinking agent. In some specific embodiments, the mass percentage of the modified phosphorus-nitrogen flame retardant hydrophilic softener in the aqueous dispersion of the modified phosphorus-nitrogen flame retardant hydrophilic softener is 6-12%, such as 7%, 8%, 9%, 10% or 11%.

[0028] In some specific embodiments, the modified phosphorus-nitrogen flame retardant hydrophilic softener is prepared by amino silicone oil through epichlorohydrin ring-opening grafting, quaternization flame retardation with phosphate quaternary ammonium salt glycerol ether, end-capping crosslinking with isocyanate propyltriethoxysilane, and hydrophilic chain extension treatment with polyether amine.

[0029] In some specific embodiments, the mass ratio of epichlorohydrin to amino silicone oil is 1:(6~12), such as 1:6, 1:7, 1:8, 1:9, 1:10, 1:11 or 1:12.

[0030] In some specific embodiments, the mass ratio of the phosphate quaternary ammonium salt glycerol ether to amino silicone oil is 1:(4~8), for example 1:4, 1:5, 1:6, 1:7 or 1:8.

[0031] In some specific embodiments, based on the mass of the amino silicone oil as 100%, the amount of isocyanate propyltriethoxysilane used is 3-6%, such as 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.

[0032] In some specific embodiments, the mass ratio of the polyetheramine to the amino silicone oil is 1:(8~12), such as 1:8, 1:9, 1:10, 1:11 or 1:12.

[0033] In some specific embodiments, the preparation method of the modified phosphorus-nitrogen flame retardant hydrophilic softener includes the following steps: (C1) Dissolve amino silicone oil in isopropanol to prepare a solution with a mass percentage of 20-30% (e.g., 20%, 22%, 24%, 26%, 28%, or 30%), add epichlorohydrin, and react at 75-95℃ (e.g., 75℃, 80℃, 85℃, 90℃, or 95℃) for 3-5 h (e.g., 3 h, 3.5 h, 4 h, 4.5 h, or 5 h). The epoxy group of epichlorohydrin undergoes a ring-opening grafting reaction with the primary amino group of the side chain of amino silicone oil, introducing active chloropropyl and hydroxyl groups onto the silicone oil molecular chain to obtain epichlorohydrin graft-modified amino silicone oil. (C2) Add phosphate quaternary ammonium salt glycerol ether to the obtained epichlorohydrin graft modified amino silicone oil, and stir the reaction at 60~80℃ (e.g. 60℃, 65℃, 70℃, 75℃ or 80℃, etc.) for 2~4 h (e.g. 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc.). The quaternary ammonium cation in the phosphate quaternary ammonium salt glycerol ether molecule undergoes a nucleophilic substitution reaction with the active chloropropyl group on the amino silicone oil. At the same time, the hydroxyl group on the glycerol ether backbone undergoes a ring-opening etherification reaction with the epoxy group on the silicone oil molecular chain. Through chemical bonds, phosphorus and nitrogen flame retardant elements and hydrophilic polyether segments are firmly introduced into the silicone oil molecular structure to obtain quaternized flame retardant hydrophilic amino silicone oil. (C3) Cool the obtained quaternized flame-retardant hydrophilic amino silicone oil to 40-50℃ (e.g., 40℃, 42℃, 44℃, 46℃, 48℃, or 50℃, etc.), and add isocyanate propyltriethoxysilane to the quaternized flame-retardant hydrophilic amino silicone oil under nitrogen protection. Stir and react for 1-2 h (e.g., 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, or 2 h, etc.). The isocyanate groups undergo addition reactions with the residual amino groups and introduced hydroxyl groups on the amino silicone oil molecular chain to form urethane bonds, introducing hydrolyzable crosslinkable silalkoxy groups at the ends of the silicone oil molecules. After the reaction is complete, add polyetheramine and stir and react for 1-2 h (e.g., 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, or 2 h, etc.) at 50-70℃ (e.g., 50℃, 55℃, 60℃, 65℃, or 70℃, etc.). (h, etc.), the terminal amino group in the polyetheramine molecule further reacts with the residual epoxy and isocyanate groups in the system to introduce additional hydrophilic polyether segments into the silicone oil molecular chain, while consuming the residual active groups to ensure the stability of the system. The solvent is removed by vacuum distillation to obtain the modified phosphorus nitrogen flame retardant hydrophilic softener.

[0034] Secondly, this application provides a method for preparing an arc-resistant fabric with flame-retardant function as described in the first aspect, the method comprising the following steps: (1) The anti-arc fabric base fabric is impregnated and dried in an aqueous solution of modified silicate chitosan flame retardant to obtain chitosan modified anti-arc fabric base fabric. (2) The chitosan-modified anti-arc fabric base obtained in step (1) is impregnated and dried in an aqueous solution of modified butanetetracarboxylic acid crosslinking agent to obtain the butanetetracarboxylic acid-modified anti-arc fabric base. (3) The butanetetracarboxylic acid modified arc-resistant fabric base obtained in step (2) is impregnated and padded in a modified phosphorus-nitrogen flame-retardant hydrophilic softener aqueous dispersion, and then dried and oven-dried to obtain the arc-resistant fabric with flame-retardant function.

[0035] In some specific embodiments, the rolling residue of the impregnation process in step (1) is 75-90%, such as 75%, 77%, 79%, 81%, 83%, 85%, 89% or 90%.

[0036] In some specific embodiments, the drying temperature in step (1) is 90~110℃, such as 90℃, 95℃, 100℃, 105℃ or 110℃.

[0037] In some specific embodiments, the drying time in step (1) is 1 to 3 minutes, for example, 1 minute, 1.5 minutes, 2 minutes, 2.5 minutes or 3 minutes.

[0038] In some specific embodiments, the immersion rolling process in step (2) is a two-immersion and two-roll process.

[0039] Preferably, the rolling residue rate of the impregnation treatment in step (2) is 70-85%, such as 70%, 72%, 74%, 76%, 78%, 80%, 82% or 85%.

[0040] In some specific embodiments, the temperature of the impregnation treatment in step (2) is 170~190℃, for example 170℃, 175℃, 180℃, 185℃ or 190℃.

[0041] In some specific embodiments, the soaking and rolling treatment time in step (2) is 2 to 4 minutes, for example, 2 minutes, 2.5 minutes, 3 minutes, 3.5 minutes or 4 minutes.

[0042] In some specific embodiments, the immersion rolling process in step (3) is a two-immersion and two-roll process.

[0043] In some specific embodiments, the rolling residue of the impregnation process in step (3) is 65-80%, for example, 65%, 70%, 75% or 80%.

[0044] In some specific embodiments, the temperature of the impregnation treatment in step (3) is 130~160℃, such as 130℃, 135℃, 140℃, 145℃, 150℃, 155℃ or 160℃.

[0045] In some specific embodiments, the soaking and rolling process in step (3) takes 4 to 6 minutes, for example, 4 minutes, 4.5 minutes, 5 minutes, 5.5 minutes or 6 minutes.

[0046] In some specific embodiments, the drying and shaping temperature in step (3) is 130~160℃, such as 130℃, 135℃, 140℃, 145℃, 150℃ or 160℃.

[0047] In some specific embodiments, the drying and shaping time in step (3) is 4 to 6 minutes, for example, 4 minutes, 4.5 minutes, 5 minutes, 5.5 minutes or 6 minutes.

[0048] Thirdly, this application provides an arc-resistant textile, which includes an arc-resistant fabric with flame-retardant function as described in the first aspect.

[0049] Compared with the prior art, this application has the following advantages: The flame-retardant arc-resistant fabric provided in this application is obtained by impregnating the arc-resistant fabric base fabric sequentially with an aqueous solution of modified silicate chitosan flame retardant, an aqueous solution of modified butanetetracarboxylic acid crosslinking agent, and an aqueous solution of modified phosphorus-nitrogen flame retardant hydrophilic softener. By limiting the specific composition of the aqueous solution of modified silicate chitosan flame retardant, the aqueous solution of modified butanetetracarboxylic acid crosslinking agent, and the aqueous dispersion of modified phosphorus-nitrogen flame retardant hydrophilic softener, the final arc-resistant fabric has high flame retardancy, high tensile strength, excellent soft hand feel, and excellent washability. Detailed Implementation

[0050] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.

[0051] Preparation Example 1-1 A modified silicate-chitosan flame retardant, the preparation method of which includes the following steps: (1) Chitosan was dissolved in an aqueous acetic acid solution with a mass percentage of 3% to prepare a chitosan solution with a mass percentage of 4%. Tetraethyl orthosilicate was added and the mixture was stirred and hydrolyzed at 40°C for 2 h to obtain silicic acid sol grafted chitosan. (2) Add polyethyleneimine (number average molecular weight of 800) to the silica sol grafted chitosan obtained in step (1), and stir at 60°C for 2 h to obtain a polyethyleneimine cross-linked silica chitosan complex. (3) Add γ-glycidyl etheroxypropyltrimethoxysilane to the silicate-chitosan complex obtained in step (2) and stir at 50°C for 1 h to obtain a surface-coupled modified composite flame retardant precursor. (4) Add phytic acid to the composite flame retardant precursor obtained in step (3), stir and react at 70°C for 2 h, and finally filter, wash and vacuum dry to obtain modified silicate chitosan flame retardant. The mass ratio of tetraethyl orthosilicate to chitosan is 1:2; the mass ratio of polyethyleneimine to chitosan is 1:3; the amount of γ-glycidyl etheroxypropyltrimethoxysilane added is 3% of the mass of chitosan; and the mass ratio of phytic acid to chitosan is 1:3.

[0052] Preparation Examples 1-2 A modified silicate-chitosan flame retardant, the preparation method of which includes the following steps: (1) Chitosan was dissolved in an aqueous acetic acid solution with a mass percentage of 4% to prepare a chitosan solution with a mass percentage of 5%. Tetraethyl orthosilicate was added and the mixture was stirred and hydrolyzed at 50°C for 3 h to obtain silicic acid sol grafted chitosan. (2) Add polyethyleneimine (number average molecular weight of 800) to the silica sol grafted chitosan obtained in step (1), and stir at 70°C for 3 h to obtain a polyethyleneimine cross-linked silica chitosan complex. (3) Add γ-glycidyl etheroxypropyltrimethoxysilane to the silicate-chitosan complex obtained in step (2) and stir at 60°C for 1.5 h to obtain a surface-coupled modified composite flame retardant precursor. (4) Add phytic acid to the composite flame retardant precursor obtained in step (3), stir and react at 80°C for 2.5 h, and finally filter, wash and vacuum dry to obtain modified silicate chitosan flame retardant. The mass ratio of tetraethyl orthosilicate to chitosan is 1:3; the mass ratio of polyethyleneimine to chitosan is 1:4.5; the amount of γ-glycidyl etheroxypropyltrimethoxysilane added is 4% of the mass of chitosan; and the mass ratio of phytic acid to chitosan is 1:4.

[0053] Preparation Examples 1-3 A modified silicate-chitosan flame retardant, the preparation method of which includes the following steps: (1) Chitosan was dissolved in an aqueous acetic acid solution with a mass percentage of 5% to prepare a chitosan solution with a mass percentage of 6%. Tetraethyl orthosilicate was added and the mixture was stirred and hydrolyzed at 60°C for 4 h to obtain silicic acid sol grafted chitosan. (2) Add polyethyleneimine (number average molecular weight of 800) to the silica sol grafted chitosan obtained in step (1) and stir at 80°C for 4 h to obtain a polyethyleneimine cross-linked silica chitosan complex. (3) Add γ-glycidyl etheroxypropyltrimethoxysilane to the silicate-chitosan complex obtained in step (2) and stir at 70°C for 2 h to obtain a surface-coupled modified composite flame retardant precursor. (4) Add phytic acid to the composite flame retardant precursor obtained in step (3), stir and react at 90°C for 3 h, and finally filter, wash and vacuum dry to obtain modified silicate chitosan flame retardant. The mass ratio of tetraethyl orthosilicate to chitosan is 1:4; the mass ratio of polyethyleneimine to chitosan is 1:6; the amount of γ-glycidyl etheroxypropyltrimethoxysilane added is 5% of the mass of chitosan; and the mass ratio of phytic acid to chitosan is 1:5.

[0054] Preparation Example 2-1 A modified butanetetracarboxylic acid crosslinking agent, the preparation method of which includes the following steps: (1) Dissolve butanetetracarboxylic acid in deionized water to prepare a solution with a mass percentage of 15%, add sodium hypophosphite, adjust the pH to 3.5, stir and dissolve at 60°C to obtain a catalytic activation system; (2) Add citric acid to the catalytic activation system obtained in step (1), stir and react at 75°C for 1.5 h, then cool down to 50°C and add polyethylene glycol 400, stir and react for 40 min to obtain polyethylene glycol grafted modified composite crosslinking agent. (3) Add N-hydroxysuccinimide to the composite crosslinking agent obtained in step (2), stir and react at 40°C for 30 min, and then cool to room temperature at a rate of 5°C / min to obtain the modified butanetetracarboxylic acid crosslinking agent; The mass ratio of sodium hypophosphite to butanetetracarboxylic acid is 1:5; the mass ratio of citric acid to butanetetracarboxylic acid is 1:4; the mass ratio of polyethylene glycol 400 to butanetetracarboxylic acid is 1:10; and the molar ratio of N-hydroxysuccinimide to butanetetracarboxylic acid is 1:3.

[0055] Preparation Example 2-2 A modified butanetetracarboxylic acid crosslinking agent, the preparation method of which includes the following steps: (1) Dissolve butanetetracarboxylic acid in deionized water to prepare a solution with a mass percentage of 20%, add sodium hypophosphite, adjust the pH to 4.0, stir and dissolve at 70°C to obtain a catalytic activation system; (2) Add citric acid to the catalytic activation system obtained in step (1), stir and react at 85°C for 2.2 h, then cool down to 57°C and add polyethylene glycol 400, stir and react for 50 min to obtain polyethylene glycol grafted modified composite crosslinking agent; (3) Add N-hydroxysuccinimide to the composite crosslinking agent obtained in step (2), stir and react at 50°C for 45 min, and then cool to room temperature at a rate of 7°C / min to obtain the modified butanetetracarboxylic acid crosslinking agent; The mass ratio of sodium hypophosphite to butanetetracarboxylic acid is 1:6.5; the mass ratio of citric acid to butanetetracarboxylic acid is 1:5; the mass ratio of polyethylene glycol 400 to butanetetracarboxylic acid is 1:12.5; and the molar ratio of N-hydroxysuccinimide to butanetetracarboxylic acid is 1:4.

[0056] Preparation Examples 2-3 A modified butanetetracarboxylic acid crosslinking agent, the preparation method of which includes the following steps: (1) Dissolve butanetetracarboxylic acid in deionized water to prepare a solution with a mass percentage of 25%, add sodium hypophosphite, adjust the pH to 4.5, stir and dissolve at 80°C to obtain a catalytic activation system; (2) Add citric acid to the catalytic activation system obtained in step (1), stir and react at 95°C for 3 h, then cool down to 65°C and add polyethylene glycol 400, stir and react for 60 min to obtain polyethylene glycol grafted modified composite crosslinking agent; (3) Add N-hydroxysuccinimide to the composite crosslinking agent obtained in step (2), stir and react at 60°C for 60 min, and then cool to room temperature at a rate of 10°C / min to obtain the modified butanetetracarboxylic acid crosslinking agent; The mass ratio of sodium hypophosphite to butanetetracarboxylic acid is 1:8; the mass ratio of citric acid to butanetetracarboxylic acid is 1:6; the mass ratio of polyethylene glycol 400 to butanetetracarboxylic acid is 1:15; and the molar ratio of N-hydroxysuccinimide to butanetetracarboxylic acid is 1:5.

[0057] Preparation Example 3-1 A modified phosphorus-nitrogen-based flame-retardant hydrophilic softener, the preparation method of which includes the following steps: (1) Dissolve amino silicone oil (Zhejiang Runhe Organosilicon New Material Co., Ltd., RH-NB-8627) in isopropanol to prepare a solution with a mass percentage of 20%, add epichlorohydrin, and react at 75°C for 3 h to obtain epichlorohydrin grafted modified amino silicone oil. (2) Add phosphate ester quaternary ammonium salt glycerol ether to the epichlorohydrin grafted modified amino silicone oil obtained in step (1), and stir at 60°C for 2 h to obtain quaternized flame retardant hydrophilic amino silicone oil. (3) Cool the quaternized flame-retardant hydrophilic amino silicone oil obtained in step (2) to 40°C, add isocyanate propyltriethoxysilane to the quaternized flame-retardant hydrophilic amino silicone oil under nitrogen protection, stir and react for 1 h, add polyetheramine after the reaction is completed, stir and react for 1 h at 50°C to obtain modified phosphorus nitrogen flame-retardant hydrophilic softener. The mass ratio of epichlorohydrin to amino silicone oil is 1:6; the mass ratio of phosphate quaternary ammonium salt glycerol ether to amino silicone oil is 1:4; the amount of cyanate propyltriethoxysilane added is 3% of the mass of amino silicone oil; and the mass ratio of polyetheramine to amino silicone oil is 1:8.

[0058] Preparation Example 3-2 A modified phosphorus-nitrogen-based flame-retardant hydrophilic softener, the preparation method of which includes the following steps: (1) Dissolve amino silicone oil (Zhejiang Runhe Organosilicon New Material Co., Ltd., RH-NB-8627) in isopropanol to prepare a solution with a mass percentage of 25%, add epichlorohydrin, and react at 85℃ for 4 h to obtain epichlorohydrin grafted modified amino silicone oil. (2) Add phosphate ester quaternary ammonium salt glycerol ether to the epichlorohydrin grafted modified amino silicone oil obtained in step (1), and stir at 70°C for 3 h to obtain quaternized flame retardant hydrophilic amino silicone oil. (3) Cool the quaternized flame-retardant hydrophilic amino silicone oil obtained in step (2) to 45°C, add isocyanate propyltriethoxysilane to the quaternized flame-retardant hydrophilic amino silicone oil under nitrogen protection, stir and react for 1.5 h, add polyetheramine after the reaction is completed, stir and react for 1.5 h at 60°C to obtain modified phosphorus nitrogen flame-retardant hydrophilic softener; The mass ratio of epichlorohydrin to amino silicone oil is 1:9; the mass ratio of phosphate quaternary ammonium salt glycerol ether to amino silicone oil is 1:6; the amount of cyanate propyltriethoxysilane added is 4.5% of the mass of amino silicone oil; and the mass ratio of polyetheramine to amino silicone oil is 1:10.

[0059] Preparation Example 3-3 A modified phosphorus-nitrogen-based flame-retardant hydrophilic softener, the preparation method of which includes the following steps: (1) Dissolve amino silicone oil (Zhejiang Runhe Organosilicon New Material Co., Ltd., RH-NB-8627) in isopropanol to prepare a solution with a mass percentage of 30%, add epichlorohydrin, and react at 95℃ for 5 h to obtain epichlorohydrin grafted modified amino silicone oil. (2) Add phosphate ester quaternary ammonium salt glycerol ether to the epichlorohydrin grafted modified amino silicone oil obtained in step (1), and stir and react at 80°C for 4 h to obtain quaternized flame retardant hydrophilic amino silicone oil. (3) Cool the quaternized flame-retardant hydrophilic amino silicone oil obtained in step (2) to 50°C, add isocyanate propyltriethoxysilane to the quaternized flame-retardant hydrophilic amino silicone oil under nitrogen protection, stir and react for 2 h, add polyetheramine after the reaction is completed, stir and react for 2 h at 70°C to obtain modified phosphorus nitrogen flame-retardant hydrophilic softener. The mass ratio of epichlorohydrin to amino silicone oil is 1:12; the mass ratio of phosphate quaternary ammonium salt glycerol ether to amino silicone oil is 1:8; the amount of cyanate propyltriethoxysilane added is 6% of the mass of amino silicone oil; and the mass ratio of polyetheramine to amino silicone oil is 1:12.

[0060] Example 1 An arc-resistant fabric with flame-retardant properties is prepared by the following steps: (1) The modified silicate chitosan flame retardant provided in Preparation Example 1-1 was mixed with deionized water to prepare an aqueous solution of modified silicate chitosan flame retardant with a mass percentage of 5%; the anti-arc fabric base (aramid / flame retardant acrylonitrile blended fabric) was immersed in the obtained modified silicate chitosan flame retardant aqueous solution, with a roll-off rate of 75%, and then pre-dried at 90°C for 1 min; (2) The modified butanetetracarboxylic acid crosslinking agent provided in Preparation Example 2-1 was mixed with deionized water to obtain an aqueous solution of modified butanetetracarboxylic acid crosslinking agent with a mass percentage of 8%; the fabric pre-dried in step (1) was immersed in the obtained aqueous solution of modified butanetetracarboxylic acid crosslinking agent for two dips and two rolls with a roll residue of 70%, and then baked at 170°C for 2 min. (3) The modified phosphorus-nitrogen flame retardant hydrophilic softener provided in Preparation Example 3-1 was mixed with deionized water to obtain a modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion with a mass percentage of 6%; the fabric baked in step (2) was immersed in the obtained modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion for two dips and two squeezes, with a squeezes rate of 65%; (4) The fabric after impregnation in step (3) is dried and shaped at 130°C for 4 min to obtain the flame-retardant anti-arc fabric.

[0061] Example 2 An arc-resistant fabric with flame-retardant properties is prepared by the following steps: (1) The modified silicate chitosan flame retardant provided in Preparation Example 1-2 was mixed with deionized water to prepare an aqueous solution of modified silicate chitosan flame retardant with a mass percentage of 10%; the anti-arc fabric base (aramid / flame retardant acrylonitrile blended fabric) was immersed in the obtained modified silicate chitosan flame retardant aqueous solution, with a roll-off rate of 82%, and then pre-dried at 100°C for 1 min; (2) The modified butanetetracarboxylic acid crosslinking agent provided in Preparation Example 2-2 was mixed with deionized water to obtain an aqueous solution of modified butanetetracarboxylic acid crosslinking agent with a mass percentage of 10%; the fabric pre-dried in step (1) was immersed in the obtained aqueous solution of modified butanetetracarboxylic acid crosslinking agent, dipped and rolled twice, with a roll residue of 77%, and then baked at 180°C for 3 min; (3) The modified phosphorus-nitrogen flame retardant hydrophilic softener provided in Preparation Example 3-2 was mixed with deionized water to obtain a modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion with a mass percentage of 9%; the fabric baked in step (2) was immersed in the obtained modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion, and then dipped and rubbed twice, with a roll-off rate of 72%; (4) The fabric after impregnation in step (3) is dried and set at 145°C for 5 min to obtain the flame-retardant anti-arc fabric.

[0062] Example 3 An arc-resistant fabric with flame-retardant properties is prepared by the following steps: (1) The modified silicate chitosan flame retardant provided in Preparation Examples 1-3 was mixed with deionized water to prepare an aqueous solution of modified silicate chitosan flame retardant with a mass percentage of 15%; the anti-arc fabric base (aramid / flame retardant acrylonitrile blended fabric) was immersed in the obtained modified silicate chitosan flame retardant aqueous solution, with a roll-off rate of 90%, and then pre-dried at 110°C for 3 min; (2) The modified butanetetracarboxylic acid crosslinking agent provided in Preparation Example 2-3 was mixed with deionized water to obtain an aqueous solution of modified butanetetracarboxylic acid crosslinking agent with a mass percentage of 12%; the fabric pre-dried in step (1) was immersed in the obtained aqueous solution of modified butanetetracarboxylic acid crosslinking agent, dipped and rolled twice, with a roll residue of 85%, and then baked at 190°C for 4 min. (3) The modified phosphorus-nitrogen flame retardant hydrophilic softener provided in Preparation Example 3-3 was mixed with deionized water to obtain a modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion with a mass percentage of 12%; the fabric baked in step (2) was immersed in the obtained modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion, and then dipped and rubbed twice, with a roll-off rate of 80%; (4) The fabric after impregnation in step (3) is dried and set at 160°C for 6 min to obtain the flame-retardant anti-arc fabric.

[0063] Example 4 An arc-resistant fabric with flame-retardant function is different from that in Example 1 in that the fabric after pre-drying in step (1) is immersed in the obtained modified butanetetracarboxylic acid crosslinking agent aqueous solution for one dip and one roll. Other substances, dosages and steps are the same as in Example 1.

[0064] Example 5 An arc-resistant fabric with flame-retardant function is different from that in Example 1 in that the fabric baked in step (2) is immersed in the obtained modified phosphorus-nitrogen flame-retardant hydrophilic softener aqueous dispersion for one dip and one roll. Other substances, dosages and steps are the same as in Example 1.

[0065] Comparative Example 1 An arc-resistant fabric, which differs from Example 1 in that chitosan is used instead of the modified silicate-chitosan flame retardant provided in Preparation Example 1-1, while the other substances, amounts and steps are the same as in Example 1.

[0066] Comparative Example 2 An arc-proof fabric, which differs from Example 1 in that butanetetracarboxylic acid is used instead of the modified butanetetracarboxylic acid crosslinking agent provided in Preparation Example 2-1, while the other substances, amounts and steps are the same as in Example 1.

[0067] Comparative Example 3 An arc-resistant fabric, which differs from Example 1 in that it uses amino silicone oil instead of the modified phosphorus-nitrogen flame-retardant hydrophilic softener provided in Preparation Example 3-1, while the other substances, amounts and steps are the same as in Example 1.

[0068] Performance testing: (1) Flame retardant performance (damage length): Tested according to the method provided in GB / T 5455-2014; (2) Water wash resistance (length of damage after 50 water washes): Tested according to the method provided in GB / T 8629-2017; (3) Fracture strength: The test shall be performed in accordance with the method provided in GB / T 3923.1-2013.

[0069] The arc-proof fabrics provided in Examples 1-5 and Comparative Examples 1-3 were tested according to the above test methods. The test results are shown in Table 1. Table 1 According to the data in Table 1: The damaged length of the arc-resistant fabrics provided in Examples 1-5 is no more than 42 mm, indicating that the fabric can quickly self-extinguish when exposed to fire, has a dense char layer, a small flame spread range, and strong heat protection capabilities; after 50 washes, the damaged length is no more than 57 mm, indicating that the flame retardant in the fabric is firmly bonded to the fiber by chemical bonds, and the flame retardant components are not easily migrated or lost after repeated washing; the breaking strength is no less than 589 N, indicating that the cross-linking treatment causes little acid hydrolytic damage to the cellulose fibers in the fabric.

[0070] Compared with Example 1, the arc-resistant fabrics provided in Comparative Examples 1 to 3 all had higher damage lengths, and the damage lengths increased significantly after 50 washes. Furthermore, their breaking strengths were all lower, indicating that the flame-retardant properties, washability, and strength of the fabrics were relatively poor.

[0071] The above description is only a specific embodiment of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in this application fall within the protection and disclosure scope of this application.

Claims

1. An arc-resistant fabric with flame-retardant properties, characterized in that, The anti-arc fabric is obtained by impregnating the anti-arc fabric base fabric in a modified silica chitosan flame retardant aqueous solution, a modified butane tetracarboxylic acid crosslinking agent aqueous solution, and a modified phosphorus nitrogen flame retardant hydrophilic softener aqueous dispersion. The raw materials for the modified silicate chitosan flame retardant aqueous solution include chitosan, tetraethyl orthosilicate, polyethyleneimine, silane coupling agent, phytic acid, and water. The raw materials for the modified butanetetracarboxylic acid crosslinking agent aqueous solution include butanetetracarboxylic acid, sodium hypophosphite, citric acid, polyethylene glycol, N-hydroxysuccinimide, and water; The raw materials for the modified phosphorus-nitrogen flame retardant hydrophilic softener aqueous dispersion include amino silicone oil, epichlorohydrin, phosphate quaternary ammonium salt glycerol ether, isocyanate propyltriethoxysilane, polyetheramine and water.

2. The flame-retardant arc-resistant fabric according to claim 1, characterized in that, The modified silicate chitosan flame retardant aqueous solution contains 5-15% by mass of the modified silicate chitosan flame retardant. And / or, the modified silicate chitosan flame retardant is prepared by grafting chitosan with tetraethyl orthosilicate sol-gel, constructing a polyethyleneimine crosslinking network, surface coupling with a silane coupling agent, and in-situ grafting polymerization with phytic acid. And / or, the mass percentage of the modified butanetetracarboxylic acid crosslinking agent in the aqueous solution of the modified butanetetracarboxylic acid crosslinking agent is 8-12%; And / or, the modified butanetetracarboxylic acid crosslinking agent is prepared by butanetetracarboxylic acid through sodium hypophosphite catalysis, co-reaction with citric acid, polyethylene glycol esterification grafting, and N-hydroxysuccinimide activation esterification treatment; And / or, the mass percentage of the modified phosphorus-nitrogen flame retardant hydrophilic softener in the aqueous dispersion of the modified phosphorus-nitrogen flame retardant hydrophilic softener is 6-12%; And / or, the modified phosphorus-nitrogen flame retardant hydrophilic softener is prepared by amino silicone oil through epichlorohydrin ring-opening grafting, quaternization flame retardant treatment with phosphate quaternary ammonium salt glycerol ether, end-capping crosslinking with isocyanate propyltriethoxysilane, and hydrophilic chain extension treatment with polyether amine.

3. The flame-retardant arc-resistant fabric according to claim 1 or 2, characterized in that, The mass ratio of tetraethyl orthosilicate to chitosan is 1:(2~4); And / or, the mass ratio of the polyethyleneimine to chitosan is 1:(3~6); And / or, based on 100% by mass of the chitosan, the amount of the silane coupling agent is 3-5%; And / or, the silane coupling agent comprises any one or a combination of at least two of γ-glycidoxypropyltrimethoxysilane, vinyltrimethoxysilane, or aminopropyltriethoxysilane; And / or, the mass ratio of phytic acid to chitosan is 1:(3~5).

4. The flame-retardant arc-resistant fabric according to any one of claims 1 to 3, characterized in that, The mass ratio of sodium hypophosphite to butanetetracarboxylic acid is 1:(5~8); And / or, the mass ratio of citric acid to butanetetracarboxylic acid is 1:(4~6); And / or, the mass ratio of the polyethylene glycol to butanetetracarboxylic acid is 1:(10~15); And / or, the molar ratio of the N-hydroxysuccinimide to butanetetracarboxylic acid is 1:(3~5); And / or, the mass ratio of epichlorohydrin to amino silicone oil is 1:(6~12); And / or, the mass ratio of the phosphate quaternary ammonium salt glycerol ether to amino silicone oil is 1:(4~8); And / or, based on 100% by mass of the amino silicone oil, the amount of isocyanate propyltriethoxysilane used is 3-6%; And / or, the mass ratio of the polyetheramine to the amino silicone oil is 1:(8~12).

5. A method for preparing an arc-resistant fabric with flame-retardant function as described in any one of claims 1 to 4, characterized in that, The preparation method includes the following steps: (1) The anti-arc fabric base fabric is impregnated and dried in an aqueous solution of modified silicate chitosan flame retardant to obtain chitosan modified anti-arc fabric base fabric. (2) The chitosan-modified anti-arc fabric base obtained in step (1) is impregnated and dried in an aqueous solution of modified butanetetracarboxylic acid crosslinking agent to obtain the butanetetracarboxylic acid-modified anti-arc fabric base. (3) The butanetetracarboxylic acid modified arc-resistant fabric base obtained in step (2) is impregnated and padded in a modified phosphorus-nitrogen flame-retardant hydrophilic softener aqueous dispersion, and then dried and oven-dried to obtain the arc-resistant fabric with flame-retardant function.

6. The preparation method according to claim 5, characterized in that, The rolling allowance in step (1) is 75-90%; And / or, the drying temperature in step (1) is 90~110℃ and the time is 1~3 min.

7. The preparation method according to claim 5 or 6, characterized in that, The immersion and rolling process in step (2) is a two-immersion and two-roll process; And / or, the roll residue of the impregnation treatment in step (2) is 70-85%; And / or, the temperature of the impregnation treatment in step (2) is 170~190℃ and the time is 2~4 min.

8. The preparation method according to any one of claims 5 to 7, characterized in that, The immersion and rolling process in step (3) is a two-dip and two-roll process; And / or, the roll residue of the impregnation treatment in step (3) is 65-80%; And / or, the temperature of the impregnation treatment in step (3) is 130~160℃ and the time is 4~6 min.

9. The preparation method according to any one of claims 5 to 8, characterized in that, The drying and shaping temperature in step (3) is 130~160℃, and the time is 4~6 min.

10. An anti-arc textile, characterized in that, The arc-resistant textile includes the arc-resistant fabric with flame-retardant function as described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Preparation method of cellulose fabric having antibacterial and inflaming-retarding functions

    CN104911910A